Effects of allopurinol and oxipurinol on purine synthesis in cultured human cells - Kelley, William N. (1970)
In the present study we have examined the effects of allopurinol and oxipurinol on the de novo synthesis of purines in cultured human fibroblasts. Allopurinol inhibits de novo purine synthesis in the absence of xanthine oxidase. Inhibition at lower concentrations of the drug requires the presence of hypoxanthine-guanine phosphoribosyltransferase as it does in vivo. Although this suggests that the inhibitory effect of allopurinol at least at the lower concentrations tested is a consequence of its conversion to the ribonucleotide form in human cells, the nucleotide derivative could not be demonstrated. Several possible indirect consequences of such a conversion were also sought. There was no evidence that allopurinol was further utilized in the synthesis of nucleic acids in these cultured human cells and no effect of either allopurinol or oxipurinol on the long-term survival of human cells in vitro could be demonstrated. At higher concentrations, both allopurinol and oxipurinol inhibit the early steps of de novo purine synthesis in the absence of either xanthine oxidase or hypoxanthine-guanine phosphoribosyltransferase. This indicates that at higher drug concentrations, inhibition is occurring by some mechanism other than those previously postulated.